Managerial learning from the perspectives of individual and organization level learning. - Maniam, Vikineswaran; Uli, Jegak; Sail, Rahim (World Business Institute, 2010)
The purpose of this research paper is to empirically investigate managerial learning from the perspective of individual and organization level learning by managers in the organizations they work for. On the premise that all organizations are learning organizations this research draws upon the data collected using an instrument developed by Moilanen (2001b) in a Malaysian scenario. Analysis of the data collected on whether there was significance difference between individual and organization level learning led to a decisive conclusion that the managers feel strongly that most learning in the organization they work for was at the individual rather than at organization level. This decisive conclusion, using stringent statistical analysis, has deep implication in that learning by managers must relate to the overall development and sustainment in building their organization as learning organizations, and not for benefits at micro level with individual effort or interpersonal level. Some suggestions are given for overall development of the learning organization through managerial learning.